Differences in prognosis and underuse of adjuvant chemotherapy between elderly and non‐elderly patients in stage III colorectal cancer. Issue 1 (26th August 2022) - Shiraishi, Takuya; Ogawa, Hiroomi; Shioi, Ikuma; Ozawa, Naoya; Osone, Katsuya; Okada, Takuhisa; Sohda, Makoto; Shirabe, Ken; Saeki, Hiroshi
Abstract: Aim: We aimed to clarify the use of adjuvant chemotherapy and the prognosis of elderly colorectal cancer patients compared with non‐elderly patients, and the usefulness of sarcopenia as an indicator for the introduction and completion of adjuvant chemotherapy. Methods: Between 2013 and 2021, 215 patients with pStage III disease were included. We investigated perioperative clinicopathological factors, adjuvant chemotherapy details, and prognosis. Preoperative sarcopenia status was evaluated using computed tomography images. Elderly patients were defined as those aged ≥70 years. Results: We included 121 (56.3%) and 94 (43.7%) non‐elderly and elderly patients, respectively. Among the elderly patients, 47 had sarcopenia. There were no significant differences in the incompletion rate of adjuvant chemotherapy between elderly and non‐elderly patients (27.1%/16.2%, P = 0.119). The most common reason for the discontinuation of adjuvant chemotherapy was side effects, regardless of age. The respective 3‐year‐disease free survival of patients with no/completed/incomplete adjuvant chemotherapy were 65.5%, 80.2%, and 57.7% for non‐elderly patients ( P = 0.045) and 73.4%, 70.6%, and 71.6% for elderly patients ( P = 0.924). The number of elderly patients with sarcopenia was significantly higher in patients without adjuvant chemotherapy ( P = 0.004) and those with incomplete adjuvant chemotherapy ( P = 0.004). The 3‐year‐disease free survival of elderly sarcopenic patients without and with adjuvant chemotherapy were 78.3% and 59.2%, respectively ( P = 0.833). Conclusion: Elderly patients did not show a benefit of adjuvant chemotherapy regardless of whether they had completed adjuvant chemotherapy, unlike non‐elderly patients. Moreover, the evaluation of preoperative sarcopenia in elderly colorectal cancer patients may be useful in determining the indication for adjuvant chemotherapy. Abstract : This study analyzed data from consecutive patients with stage III colorectal cancer following curative resection and examined the reason for not introducing adjuvant chemotherapy (AC) and the differences in prognosis between completed and incomplete AC in elderly and non‐elderly patients. Furthermore, this study also looked into the usefulness of sarcopenia as an indicator for the introduction and completion of AC.